Development and Implementation of an RFID-Based Tunnel Access Monitoring System - Kai Kordelin; Jaana Kordelin; Markku Johansson; Johanna Virkki; Leena Ukkonen; Lauri Sydänheimo (Science and Technology of Nuclear Installations)
Due to safety reasons, the exact number and location of people working in an underground tunnel need to be known all the time. This work introduces the development and implementation of an RFID-based access monitoring system for the ONKALO nuclear waste storage facility. This system was taken into use in 2010 and was systematically monitored for one year. The system principle and the used equipment are presented in this paper together with the reliability evaluation results of the implemented system. According to the field use evaluation of the ready system, the reading reliability at the end of the monitoring period was 100%. In addition, even after the successful monitoring period, the system has been updated and new features for safety improvement have been created based on fire department guidelines and achieved user experience. In the future, the RFID system has been planned to be used also in the final depositing of the used nuclear fuel and buffer materials.